Trends in Real-World Neovascular AMD Treatment Outcomes in the UK - Mehta, Hemal (Clin Ophthalmol, 2020)
PURPOSE: To report trends in real-world outcomes of anti-vascular endothelial growth factor (anti-VEGF) therapy for neovascular age-related macular degeneration (nAMD) in the United Kingdom (UK) over the last decade. DESIGN: Systematic review. METHODS: Medline, PubMed, and Embase databases were searched from 9 April 2010 to 8 April 2020 for publications that met the inclusion criteria: treatment-naïve eyes, UK-only data and ≥1 year of follow-up. ICHOM (International Consortium for Health Outcome Measures) outcomes and study quality were assessed. Visual acuity (VA) trends were assessed in studies with ≥100 eyes at baseline. RESULTS: Twenty-six studies (n=25,761 eyes) were included, meeting 14–17 out of 20 Institute of Health Economics Quality Appraisal of Case Series checklist domains. Only ranibizumab and aflibercept outcome data were available. The mean injection number in the first year of treatment was 5.9 in publications from 2010 to 2015 and 7.1 from 2015 to 2020. Average baseline VA and mean one-year, two-year and three-year VA gains gradually improved over the last decade. Longer-term studies reported that the visual gains achieved in the first year of treatment were rarely maintained, with under-treatment a likely contributing factor. CONCLUSION: UK real-world outcomes have improved over the last decade with improved service delivery and the adoption of more proactive treatment regimens but are still not always as impressive as registration clinical trial results. Access to longer-acting anti-VEGF therapies would reduce the treatment burden for patients, carers, and the healthcare system, potentially making replication of clinical trial results possible in the NHS.